Tropical cyanobacteria and their biotechnological applications - Rigonato, Janaina; Alvarenga, Danillo Oliveira [UNESP]; Fiore, Marli Fátima (Springer Nature, 2017)
Tropical environments have favorable conditions that allow the development of a great diversity of microorganisms. Among the tropical microbial community, cyanobacteria are observed colonizing a great variety of niches, from desert to forest biomes. These organisms play important ecological roles in such environments, since they have the ability to carry out oxygenic photosynthesis and act as primary producers, while some are also able to fix atmospheric nitrogen and become important sources of this element. In addition, cyanobacteria present huge potential for producing metabolites of biotechnological interest in the food, agricultural, and pharmaceutical industries. However, the diversity of cyanobacteria in tropical zones is still underestimated, and studies on these organisms in countries like Brazil are mostly focused on a few regions, leaving several territories in need of deeper exploration. In this chapter, the diversity and biotechnological applications of cyanobacteria from tropical environments will be explored.
Keywords: Bioactivity; Brazilian biomes; Cyanopeptides; Diversity; Ecosystems; Natural products; Systematics